Low-gloss fluoride-free flame-retardant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) resin composition as well as preparation method and application thereof

Through the synergistic effect of crosslinking masterbatch and UHMWPE, combined with phosphazene flame retardant and silicone acrylate core-shell toughener, the environmental and health threats of PFAS in flame retardant PC/ABS resin system are solved, achieving high efficiency The V-0 flame retardant grade and low gloss reduce production costs and are suitable for a variety of application scenarios.

CN119161714AInactive Publication Date: 2024-12-20PANSU TECHNOLOGY (JIANGSU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411588864.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing flame retardant PC/ABS resin system contains perfluoro and polyfluoroalkyl compounds (PFAS), which poses a threat to the environment and health. At the same time, the flame retardant grade is low, fusible droplets, high cost and high gloss.

Method used

Using low-gloss, fluorine-free flame retardant PC/ABS resin composition, the synergistic effect of cross-linked masterbatches and UHMWPE can improve the flame retardant grade, control the droplet phenomenon, and reduce production costs, using phosphazene flame retardant and silicone acrylic acid Ester core-shell tougheners are used to replace high-cost silicone flame retardants.

Benefits of technology

Achieve V-0 flame retardant grade, low gloss effect, while maintaining excellent mechanical properties, reducing the modification cost of fluorine-free flame retardant PC/ABS system, adapting to the global trend of PFAS control, and suitable for automobiles, electronic products and Furniture decoration and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125010880000021
    Figure BDA0005125010880000021
  • Figure BDA0005125010880000022
    Figure BDA0005125010880000022
  • Figure BDA0005125010880000031
    Figure BDA0005125010880000031
Patent Text Reader

Abstract

The invention relates to a low-gloss fluoride-free flame-retardant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) resin composition as well as a preparation method and application thereof. The resin composition is prepared from the following components in parts by weight: 70 to 90 parts of PC (Polycarbonate) resin, 5 to 10 parts of ABS (Acrylonitrile Butadiene Styrene) resin, 8 to 12 parts of phosphazene flame retardant, 2 to 5 parts of flexibilizer, 3 to 6 parts of crosslinking master batch, 1 to 3 parts of UHMWPE (Ultra High Molecular Weight Polyethylene) and 0.5 to 1.5 parts of auxiliary agent. The preparation method comprises the following steps: stirring and fully mixing the raw materials in a high-speed mixer, and carrying out material melting, mixing, homogenizing, bracing, cooling and pelletizing under the conveying, shearing and mixing of screws by a twin-screw extruder to obtain the low-gloss fluoride-free flame-retardant PC / ABS resin composition. The resin composition not only has excellent flame retardant property, but also has excellent mechanical properties and ultralow glossiness, can meet the environmental protection requirements of PFAS prohibited instructions, and is suitable for being applied to the fields of electric tools, rear shells of televisions, OA (office equipment), new energy batteries, electronics and electrical appliances, household appliances and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a low-gloss fluorine-free flame-retardant PC / ABS resin composition and a preparation method and application thereof. Background Art

[0002] Polycarbonate resin (PC) has the advantages of flame retardancy, high heat resistance, high impact resistance, high transparency, and high dimensional stability. It is widely used in electronics and electrical, new energy batteries, home appliances, office equipment and other industries.

[0003] PC resin has excellent flame retardancy and can meet the UL V-2 flame retardant standard. Its limiting oxygen index is as high as 21%-24%. However, PC resin is easy to melt and drip during combustion. Therefore, high molecular weight polytetrafluoroethylene (PTFE) is usually added as an anti-dripping agent in flame retardant modification to achieve the V-0 flame retardant requirement. However, PTFE, as a core flame retardant system component, inevitably contains perfluorinated and polyfluoroalkyl compounds (PFAS) during the polymerization process. Its chemical structure (CF bond) is extremely stable and can withstand high temperature, light, chemical action, microbial action, and the metabolism of higher vertebrates. It is called a "permanent chemical" and will accumulate permanently in the human body, posing a direct threat to health. At the same time, studies have shown that PFAS pollution is exacerbating the global biodiversity crisis. Therefore, the US Environmental Protection Agency and the European Union have gradually strengthened control measures on PFAS, so alternatives to PTFE, which is commonly used in flame-retardant PC alloys, urgently need to be studied and broken through.

[0004] Scientists are currently conducting research on new PC / ABS flame retardant systems, hoping that they can replace the gap left by PTFE. Currently, the more successful cases are silicone flame retardant systems such as silicone copolymer PC and silicone flame retardants, but pure systems of this type will increase the modification cost by a huge amount.

[0005] PC resin itself has excellent gloss, but it will cause trouble in low-gloss applications. It is not easy to reduce the gloss of PC. Usually, the most common commercial method is to add Chemtura's matte agent, similar to semi-crosslinked SAN (styrene-acrylonitrile copolymer), but this type of solution has a greater impact on PC impact toughness. There are also functional group chain extenders, such as GMA (glycidyl methacrylate) functionalized SAN to reduce PC gloss, but this type of solution will greatly reduce fluidity and affect processing performance, and the extent of gloss reduction is also limited.

[0006] Therefore, a new solution is urgently needed for preparing a low-gloss fluorine-free flame-retardant PC / ABS resin composition. Summary of the invention

[0007] The purpose of the present invention is to provide a low-gloss fluorine-free flame-retardant PC / ABS resin composition and its preparation method and application, so as to overcome the technical defects of the flame-retardant PC / ABS system without PTFE in the prior art, such as low flame retardancy, easy melting drop, high cost and high gloss.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] In one aspect, the present invention provides a low-gloss fluorine-free flame-retardant PC / ABS resin composition, comprising the following components in parts by weight:

[0010]

[0011] Preferably, the PC resin is bucket-grade PC, and the melt index of the PC resin at 300° C. and a load of 1.2 kg is 2-5 g / 10 min.

[0012] Further preferably, the bucket-grade PC resin refers to a polycarbonate PC material that can be used to manufacture drinking water buckets. This material needs to meet food contact safety standards and have excellent transparency, heat resistance, impact resistance, and dimensional stability.

[0013] More preferably, the melt index of the PC resin is 2-3 g / 10 min.

[0014] Preferably, the ABS resin has a melt index of 5-10 g / 10 min at 220° C. and a load of 10 kg.

[0015] Further preferably, the melt index of the ABS resin is 5-8 g / 10 min.

[0016] Preferably, the phosphorus content of the phosphazene flame retardant is greater than 13 wt%.

[0017] Further preferably, the phosphazene flame retardant includes hexaphenoxy cyclophosphazene.

[0018] Preferably, the crosslinking masterbatch comprises the following components in parts by weight:

[0019]

[0020]

[0021] Further preferably, the SAN resin has a melt index of 10-30 g / min at 220° C. and a load of 10 kg.

[0022] Further preferably, the melt index of the SAN resin is 15-25 g / min.

[0023] More preferably, the weight average molecular weight of the styrene-maleic anhydride copolymer (SMA) is 80,000-120,000.

[0024] Further preferably, the content of maleic anhydride in the styrene-maleic anhydride copolymer is 18 wt%-25 wt%.

[0025] Further preferably, the weight average molecular weight of the styrene-glycidyl methacrylate copolymer (PS-g-GMA) is 80,000-150,000, and the GMA content thereof is 10 wt%-40 wt%.

[0026] Further preferably, the rubber content of the MBS (methyl methacrylate-butadiene-styrene terpolymer) is 50%-70%, and the rubber particle size is 200-350 nm.

[0027] Further preferably, the antioxidant is B900 and the lubricant is PETS.

[0028] Preferably, the weight average molecular weight of the UHMWPE (ultra-high molecular weight polyethylene) is 1.5 million to 5 million.

[0029] More preferably, the weight average molecular weight of the UHMWPE is 2-5 million.

[0030] Preferably, the auxiliary agent is selected from a mixture of one or more of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene bis stearamide, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber.

[0031] Preferably, the toughening agent is a silicon-containing acrylic core-shell toughening agent.

[0032] Further preferably, the silicon-containing acrylate core-shell toughening agent has silicone acrylate rubber as the core.

[0033] Further preferably, the content of the silicone acrylate rubber is 50wt%-65wt%.

[0034] More preferably, the particle size of the silicone acrylate rubber is 150nm-300nm.

[0035] Further preferably, the silicone acrylate rubber has a silicon content of 20wt%-50wt%.

[0036] Further preferably, the shell of the silicon-containing acrylic core-shell toughening agent is methyl methacrylate-styrene copolymer.

[0037] In a second aspect, the present invention provides a method for preparing the above-mentioned low-gloss fluorine-free flame-retardant PC / ABS resin composition, comprising the following steps:

[0038] S1. Mix SAN resin, styrene-maleic anhydride copolymer, styrene-glycidyl methacrylate copolymer, MBS, antioxidant and lubricant by weight for 5-15 minutes, and feed into a twin-screw extruder. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the cross-linked masterbatch;

[0039] S2. Mix PC resin, ABS resin, phosphazene flame retardant, toughening agent, cross-linked masterbatch obtained in step S1, UHMWPE and processing aid by weight for 5 to 15 minutes, and feed into a twin-screw extruder. Under the conveying, shearing and mixing of the screw, the material is melted, homogenized, drawn, cooled and pelletized to obtain the low-gloss fluorine-free flame-retardant PC / ABS resin composition.

[0040] Further preferably, in step S1, the mixing is performed in a high-speed mixer, and the rotation speed of the high-speed mixer is 300-500 rpm.

[0041] Further preferably, in step S1, the screw length-to-diameter ratio of the twin-screw extruder is (35-50):1, and the twin-screw extruder is equipped with a temperature control device and a vacuum pumping device.

[0042] Further preferably, in step S1, the extrusion temperature of the twin-screw extruder is 210-230° C., and the screw speed is 200-400 rpm.

[0043] Further preferably, in step S2, the mixing is performed in a high-speed mixer, and the rotation speed of the high-speed mixer is 300-500 rpm.

[0044] Further preferably, in step S2, the screw length-to-diameter ratio of the twin-screw extruder is (35-50):1, and the twin-screw extruder is equipped with a temperature control device and a vacuum pumping device.

[0045] Further preferably, in step S2, the extrusion temperature of the twin-screw extruder is 250-270° C., and the screw speed is 300-500 rpm.

[0046] In a third aspect, the present invention provides an application of the low-gloss fluorine-free flame-retardant PC / ABS resin composition in automobiles, electronic products, and furniture decoration.

[0047] Further preferably, the low-gloss fluorine-free flame-retardant PC / ABS resin composition can be used for dashboards, door panels, and center control panels in automobile interiors to reduce driver visual fatigue and improve driving safety.

[0048] Further preferably, the low-gloss fluorine-free flame-retardant PC / ABS resin composition can be used for housings and screens of mobile phones and tablet computers to reduce glare interference and improve the visual comfort of users.

[0049] Further preferably, the low-gloss fluorine-free flame-retardant PC / ABS resin composition can be used for matte building material floors and decorative strips to improve home comfort.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The low-gloss fluorine-free flame-retardant PC / ABS resin composition of the present invention improves the flame retardancy level through the synergistic effect of the cross-linked masterbatch and UHMWPE, making the flame-retardant PC / ABS less likely to drip during combustion, and also brings a low-gloss effect, while reducing the modification cost of the fluorine-free flame-retardant PC / ABS system.

[0052] (2) The low-gloss fluorine-free flame-retardant PC / ABS resin composition of the present invention uses a cross-linked masterbatch and UHMWPE to produce a good flame-retardant synergistic effect, which can effectively control the dripping phenomenon of the flame-retardant PC / ABS during the combustion process, play an anti-dripping effect similar to PTFE, and achieve a V-0 flame retardant grade.

[0053] (3) The low-gloss fluorine-free flame-retardant PC / ABS resin composition of the present invention has a synergistic effect between the cross-linked masterbatch and UHMWPE, so that the PC / ABS resin composition has a lower gloss while still maintaining excellent mechanical properties, and has a higher impact strength, tensile strength and melt index.

[0054] (4) The low-gloss fluorine-free flame-retardant PC / ABS resin composition of the present invention replaces the use of high-cost silicone flame retardants to improve the flame retardancy of the PC / ABS resin composition through the synergistic effect between the cross-linked masterbatch and UHMWPE, thereby reducing the production cost and providing a new solution for a halogen-free and fluorine-free flame-retardant PC / ABS system with excellent mechanical properties. DETAILED DESCRIPTION

[0055] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0056] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0057] The components and characteristics involved in the embodiments and comparative examples of the present invention are as follows:

[0058] PC resin, M7027, Sinopec Mitsubishi, melt index 3g / 10min;

[0059] ABS resin, ABS3504, Gaoqiao Petrochemical, melt index 6.5g / 10min;

[0060] Phosphazene flame retardant, WSFR-5101, Zhejiang Wansheng;

[0061] Toughening agent, S2030, Mitsubishi Chemical, Japan;

[0062] SAN, SAN 128, Zhenjiang Chimei;

[0063] SMA700, Jiaxing Huawen;

[0064] SMA800, MAH content 8%, Jiaxing Huawen;

[0065] PS-g-GMA, SG-20, Jiayirong;

[0066] MBS, EM500, LG Chem;

[0067] UHMWPE, U030, Korea Petrochemical, weight average molecular weight 3 million;

[0068] HDPE (high-density polyethylene), 5000S, Yanshan Petrochemical;

[0069] Antioxidant, Irganox B900, BASF;

[0070] Lubricant, PETS, AHS, Italian hair base.

[0071] Table 1 Component ratio of cross-linked masterbatch-A, cross-linked masterbatch-B and cross-linked masterbatch-C

[0072]

[0073] Table 2 Composition of Examples 1 to 6 and Comparative Examples 1 to 7

[0074]

[0075] Examples 1 to 6 and Comparative Examples 1 to 7

[0076] A low-gloss fluorine-free flame-retardant PC / ABS resin composition, the preparation process of which is as follows:

[0077] (1) SAN resin, SMA, PS-g-GMA, MBS, antioxidant and lubricant were mixed in a high-speed mixer for 10 minutes according to the component ratio of the cross-linking masterbatch shown in Table 1, and then fed into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials were melted, homogenized, drawn, cooled and pelletized to obtain a cross-linking masterbatch.

[0078] The twin-screw extruder has a screw length-to-diameter ratio of 40:1 and is equipped with a temperature control device and a vacuum device. The extrusion temperature of the twin-screw extruder is 210-230°C and the screw speed is 300 rpm.

[0079] (2) PC resin, ABS resin, phosphazene flame retardant, toughening agent, crosslinking masterbatch, UHMWPE and additives were mixed in a high-speed mixer for 10 minutes according to the component ratio of the crosslinking masterbatch shown in Table 2, and then fed into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials were melted, homogenized, drawn, cooled and pelletized to obtain a low-gloss fluorine-free flame-retardant PC / ABS resin composition.

[0080] The twin-screw extruder has a screw length-to-diameter ratio of 40:1 and is equipped with a temperature control device and a vacuum device. The extrusion temperature of the twin-screw extruder is 250-270°C and the screw speed is 400 rpm.

[0081] The fluorine-free flame-retardant PC / ABS resin compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to performance tests. The test results are shown in Table 3.

[0082] The test methods of various embodiments and comparative examples are described as follows:

[0083] The tensile strength test was carried out according to ASTM D638 standard, and the test speed was 50 mm / min.

[0084] The notched impact strength test was carried out according to ASTM D256.

[0085] The melt index test was carried out according to ASTM D1238 standard, with a load of 5 kg and a test temperature of 240°C.

[0086] The flame retardant test is carried out according to UL94 standard.

[0087] The gloss test is carried out according to ASTM D523 standard.

[0088] Table 3 Performance of Examples 1 to 6 and Comparative Examples 1 to 7

[0089]

[0090] It can be seen from each embodiment 1-6 in Table 1 that the present invention uses cross-linked masterbatch and UHMWPE to produce a good flame retardant synergistic effect, can effectively control the melting drop phenomenon of flame retardant PC / ABS during the combustion process, play an anti-dripping effect similar to PTFE, achieve V-0 flame retardant grade, low gloss, and also have excellent mechanical properties. Comparison of Examples 1 to 3 and Examples 4-6 shows that the cross-linked masterbatch-B prepared with high content of SMA and PS-g-GMA can further reduce the surface gloss of the system, but at the same time its impact will be affected to a certain extent. From Comparative Examples 1-7, it can be seen that the single use of cross-linked masterbatch or UHMWPE cannot achieve a stable flame retardant effect, and can only reach a V-2 flame retardant grade. From Comparative Example 6, it can be seen that cross-linked masterbatch-B and HDPE do not have a flame retardant synergistic effect, and the V-0 flame retardant grade cannot be achieved. Comparative Example 7 shows that the flame retardant effect of the cross-linked masterbatch prepared by SMA with a low MAH content does not reach the V-0 grade, and the gloss is also relatively high. A high content of cross-linked masterbatch-B can also achieve a flame retardant grade of V-1 and a lower gloss, but it will sharply deteriorate the impact strength of flame-retardant PC / ABS.

[0091] The low-gloss fluorine-free flame-retardant PC / ABS resin composition of the present invention not only has excellent flame retardant properties, but also has excellent mechanical properties, and at the same time has ultra-low gloss and cost, and can actively adapt to the increasingly stringent trend of PFAS control worldwide, and the low-gloss fluorine-free flame-retardant PC / ABS resin composition is suitable for application in power tools, TV back shells, OA (office equipment), new energy batteries, electronic appliances, home appliances and other fields.

[0092] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A low-gloss fluorine-free flame-retardant PC / ABS resin composition, It is characterized in that The composition comprises the following components in parts by weight:

2. A low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The PC resin is bucket-grade PC, and the melt index of the PC resin at 300° C. and a load of 1.2 kg is 2-5 g / 10 min.

3. A low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The ABS resin has a melt index of 5-10 g / 10 min at 220° C. and a load of 10 kg.

4. A low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The phosphorus content of the phosphazene flame retardant is greater than 13 wt %, and the phosphazene flame retardant includes hexaphenoxy cyclophosphazene.

5. The low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The crosslinked masterbatch comprises the following components in parts by weight:

6. A low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 5, It is characterized in that The melt index of the SAN resin at 220° C. and 10 kg load is 10-30 g / min, the maleic anhydride content in the styrene-maleic anhydride copolymer is 18 wt %-25 wt %, and the GMA content in the styrene-glycidyl methacrylate copolymer is 10 wt %-40 wt %.

7. The low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The weight average molecular weight of the UHMWPE is 1.5 million to 5 million.

8. The low-gloss fluorine-free flame-retardant PC / ABS resin composition according to claim 1, It is characterized in that The auxiliary agent is selected from a mixture of one or more of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene bis stearamide, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber; The toughening agent is a silicon-containing acrylate core-shell toughening agent, wherein the organic silicon acrylate rubber is used as the core, the content thereof is 50wt%-65wt%, the particle size is 150nm-300nm, and the silicon content thereof is 20wt%-50wt%.

9. A method for preparing the low-gloss fluorine-free flame-retardant PC / ABS resin composition according to any one of claims 1 to 8, It is characterized in that The following steps are involved: S1. Mix SAN resin, styrene-maleic anhydride copolymer, styrene-glycidyl methacrylate copolymer, MBS, antioxidant and lubricant by weight for 5-15 minutes, and feed into a twin-screw extruder. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the cross-linked masterbatch; S2. Mix PC resin, ABS resin, phosphazene flame retardant, toughening agent, cross-linked masterbatch obtained in step S1, UHMWPE and processing aid by weight for 5 to 15 minutes, and feed into a twin-screw extruder. Under the conveying, shearing and mixing of the screw, the material is melted, homogenized, drawn, cooled and pelletized to obtain the low-gloss fluorine-free flame-retardant PC / ABS resin composition.

10. Use of the low-gloss fluorine-free flame-retardant PC / ABS resin composition according to any one of claims 1 to 8 in automobiles, electronic products and furniture decoration.

Citation Information

Cited By

  • Fluoride-free flame-retardant engineering plastic alloy and preparation method thereof

    CN121227001A

  • Fluorine-free flame-retardant PC / ABS material with high recovery ratio and preparation method thereof

    CN122167982A